Synergistic and Pharmacotherapeutic Effects of Gemcitabine and Cisplatin Combined Administration on Biliary Tract Cancer Cell Lines - Yasunari Sakamoto; Seri Yamagishi; Takuji Okusaka; Hidenori Ojima (Cells, 2019)
Gemcitabine (GEM) and cisplatin (CDDP) combination therapy (GC) is the standard chemotherapy for advanced biliary tract cancer (BTC); however, its pharmacotherapeutic efficacy remains unclear. To investigate the effects of GC, we selected 11 from 17 BTC cell lines, according to their GEM sensitivity, to be assessed using the MTS assay. The presence of synergistic effects of GC was determined using the Bliss additivism model (BM) and the combination index (CI) at a GEM:CDDP molar ratio of 7:1; this ratio was based on the respective human renal clearances of the two drugs. The pharmacotherapeutic effects were evaluated by comparing the IC50 values for administrations of GEM alone and GC in combination. All cell lines showed synergistic effects when analyzed using the BM. Based on the CI values, strong synergism, synergism, and additive effects were seen in four, five, and two cell lines, respectively. For all four GEM-resistant cell lines, on which GC had strong synergistic effects, the pharmacotherapeutic effects of GC were disappointing, with all IC50 values > 1 µM. For the GEM-effective cell lines, on which GC had synergistic or additive effects, the IC50 values were all <1 µM, and the differences were small between the IC50s for administration of GEM alone and GC in combination. Our results suggest that GC has synergistic effects on BTC cell lines but that its pharmacotherapeutic effects are inadequate.